Preliminary Study on Leaching Capacity of Rare Earth Elements from Coal Fly Ash by Using Citric Acid Solution - Gilbert Winoto; Panut Mulyono; Suyanti Suyanti; Agus Prasetya (Indonesian Journal of Chemistry)
Rare earth elements (REEs) are chemical elements in the III B and lanthanide groups on the chemical periodic table. Extracting REEs from secondary resources (such as coal fly ash) could be environmentally friendlier than extracting REEs from primary resources. Coal fly ash was chosen because of its attractive REE availability and to minimize the pollution problem created by coal fly ash dumping. Citric acid is used as the leaching agent because of its biodegradability, relatively safe vis-à-vis mineral acid commonly used in the REE leaching, and its non-damaging nature to coal fly ash’s properties as construction material. The leaching experiment was conducted at temperature variations of 30, 50, and 85 °C, with liquid-solid ratio (L/S) of 5, 10, and 15 mL/g in 50 mL of 0.01 mol/L citric acid solution. The leaching experiments were conducted in a water bath shaker. It was found that increasing L/S and temperature mainly contributed to increasing cerium leaching capacity.